MONETARY SOVEREIGNTY - Grigor Chobanyan (State and Law, 2020)
The article is devoted to the contemporary issues of monetary sovereignty in the frameworks of public international law. Particularly, the article addresses the historical evolution of the concept of monetary sovereignty, then it represents the main elements of the contemporary monetary sovereignty. The article discusses the issues of monetary sovereignty in the light of contemporary economic and legal restrictions. The author tried to show that monetary sovereignty is still one of the important features of modern sovereign state, meanwhile, the concept needs constant modifications in order to provide economic stability for the countries.